1989
DOI: 10.1161/01.hyp.13.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Baroreceptor influences on oxytocin and vasopressin secretion.

Abstract: The objective of these studies was to investigate the role of arterial baroreceptors in the control of neurohypophyseal secretion. The effect of sinoaortic denervation on basal and osmoticinduced release of oxytocin and vasopressin and on blood pressure was determined. Hypertonic or isotonic saline was infused intravenously into sham-operated or denervated rats 3 days after surgery. Plasma oxytocin and vasopressin were measured at 5 and 15 minutes after the infusion. The control levels of oxytocin were increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
2
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 22 publications
1
45
2
1
Order By: Relevance
“…Indeed, a previous study demonstrated that SAD did not change OT and VP mRNA expression within the SON and did not change the plasma levels of these hormones in rats maintained under tap water drinking (36), a condition similar to that of the present study. Sinoaortic denervation also did not prevent neurohypophyseal secretion but maintained its ability to cause modest or strong OT and VP release after isotonic or osmotic and hypovolemic stimuli, respectively (31,36,41,42). The differential effects of SAD on OT content within PVN neurons (i.e., a marked reduction) and SON neurons (i.e., no change) indicated the specificity of baroreceptors and chemoreceptors in driving the PVN OTergic neurons that modulate autonomic control and not the regulation of fluid balance by the SON OTergic pathway.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, a previous study demonstrated that SAD did not change OT and VP mRNA expression within the SON and did not change the plasma levels of these hormones in rats maintained under tap water drinking (36), a condition similar to that of the present study. Sinoaortic denervation also did not prevent neurohypophyseal secretion but maintained its ability to cause modest or strong OT and VP release after isotonic or osmotic and hypovolemic stimuli, respectively (31,36,41,42). The differential effects of SAD on OT content within PVN neurons (i.e., a marked reduction) and SON neurons (i.e., no change) indicated the specificity of baroreceptors and chemoreceptors in driving the PVN OTergic neurons that modulate autonomic control and not the regulation of fluid balance by the SON OTergic pathway.…”
Section: Discussionmentioning
confidence: 87%
“…8 pg/ml. The RIA was performed, as previously described (Morris & Alexander 1989), using a specific antiserum, which was a generous gift from Dr Mariana Morris from Wright State University (OH, USA), a standard from Bachem-Peninsula Labs (San Carlos, CA, USA) and a secondary antibody produced by Dr Franci's Laboratory (School of Medicine of Ribeirão Preto, University of São Paulo, Brazil). The results were reported as meansGS.E.M.…”
Section: Hormone Measurementmentioning
confidence: 99%
“…With a marked decrease in blood volume or blood pressure, the baroreceptor mechanism can cause secretion of large quantities of vasopressin from the posterior pituitary. 5 - 8 Other less potent stimuli of magnocellular vasopressin secretion include fever and emesis. 6 High levels of plasma vasopressin cause arteriolar vasoconstriction, although vasopressin may also cause local vasodilation in the arteries of the forearm.…”
Section: Transgenic Mouse Models Of Vasopressin Expressionmentioning
confidence: 99%